Effect of work discipline, work facilities, and motivation on employee performance at PT. Dirgantara Indonesia - Rusmana, Syffa Salsabila Putri; Siddiq, Andhika Mochamad; Ridlwan, Muttaqin (Institute of Computer Science (IOCS), 2025)
The purpose of this study is to examine how employee performance at PT. Dirgantara Indonesia is impacted by work facilities, motivation, and discipline. This study combines a descriptive and verification technique with a quantitative methodology. using articles and literature reviews as secondary data sources. This study used nonprobability sampling approaches to choose 100 employees of PT. Dirgantara Indonesia as the population and sample. Verification analysis, multiple linear regression analysis, traditional assumption tests, and hypothesis testing were among the data analysis methods employed. The results of the study show that partially and simultaneously work discipline, work facilities, and motivation have a positive and significant effect on employee performance.